Depletion of neutrophils blocks the recruitment of antigen-nonspecific cells into the liver without affecting the antiviral activity of hepatitis B virus-specific cytotoxic T lymphocytes - Sitia, Giovanni (The National Academy of Sciences, 2002)
Using transgenic mice that replicate hepatitis B virus (HBV) in their livers, we previously showed that passively transferred HBV-specific cytotoxic T cells (CTLs) recruit antigen-nonspecific lymphomononuclear and polymorphonuclear inflammatory cells that contribute to the pathogenesis of liver disease. This process is chemokine-dependent, because we recently showed that blocking the chemokines CXCL9 and CXCL10 reduces the recruitment of antigen-nonspecific lymphomononuclear cells and the severity of liver disease after CTL injection. In the current study we show that the severity of the CTL-initiated liver disease is also ameliorated by the depletion of neutrophils. Interestingly, depletion of neutrophils does not affect the intrahepatic migration or antiviral activity of CTLs, but it profoundly inhibits the recruitment of all antigen-nonspecific cells into the liver. This effect occurs in face of high intrahepatic levels of chemokine gene expression, suggesting that neutrophil-dependent functions other than chemokine induction are necessary for the recruitment process to occur. The notion that depletion of neutrophils is associated with maintenance of antiviral effects but diminished tissue damage may be significant for the development of immunotherapeutic approaches for the treatment of chronic HBV infection.